Effective leadership among committee members of neighborhood associations in a Malaysian multicultural community - Mohamad, Madinah (2012)
How can a Neighborhood Committee Member become a more effective community leader? This is a qualitative research that examines effective leadership in the context of a Malaysian community. Effective leadership is explained through various theories such as traits, behavioral, situational and emerging leadership theories. In the contexts of this study, effective leadership is linked to community development, where leaders play the critical role in improving the community economically, socially, culturally and spiritually. In answering the main research question, data are gathered qualitatively through focus group interviews and also in-depth interviews. The focus interviews involved six groups of committee members of the Malaysian Neighborhood Associations or locally known as Rukun Tetangga in the Klang Valley area while the in-depth interviews include eight selected Chairmen of the Neighborhood Associations in the state of Penang. The data from both interviews were recorded, coded and analyzed using the qualitative method. Some of the major findings of the research are: (1) The respondents became community leaders because of a strong desire to serve the community, a strong motivation to want to do something, a strong interest in becoming community leaders, a great interest in participating in voluntary activities and good support from family members and friends; (2) The community leaders performed various leadership roles such as being a change agent, problem solver, manager, communicator, negotiator and resource-linker and leading a multiracial society; (3) In leading a community, the participative leadership style is considered more desirable. In performing their roles as leaders, there is a strong need to involve others in the process. Involvement of people such as the committee members of the association, members of the community and other relevant parties will ensure better results. (4) The research has identified various competencies required by community leaders in Malaysia that include problem-solving skills, living skills in a multi-racial community, communication and interpersonal skills, decision-making skills, skills in bringing about change, skills related to conflict resolution, team-work skills, social and volunteer work skills, skills in acquiring funds and resources, skills in conducting programs for the community, skills in developing good values and leadership practices and ICT skills. The competencies are not very different from competencies identified for leaders in other situations such as public and private organizations. These are some competencies that are common to all leaders in most situations such as the abilities to communicate effectively, work in teams, manage, bring change, develop others, build and maintain relationships, lead diversity and differences and develop good values and leadership practices. The only major difference is the context of leadership, and in this study it focuses on community leadership in a multi-racial society. Hence the main role of leadership is to build a strong, peaceful and united community and thus competencies related to leading diversity and differences is one of the keys to the success of community leadership.Based on the findings of the study, community leadership effectiveness can be improved through systematic training and development of leaders.